Improving Translation Quality By Using Ensemble Approach - Chopra, D.; Joshi, N.; Mathur, I. (Engineering, Technology & Applied Science Research, 2018)
Machine translation (MT) has been a topic of great research during the last sixty years, but, improving its quality is still considered an open problem. In the current paper, we will discuss improvements in MT quality by the use of the ensemble approach. We performed MT from English to Hindi using 6 MT different engines described in this paper. We found that the quality of MT is improved by using a combination of various approaches as compared to the simple baseline approach for performing MT from source to target text.